Plural Values and Environmental Valuation. (1st February 1997) - Beckerman, Wilfred; Pasek, Joanna
The paper discusses some of the criticisms of contingent valuation (CV) and allied techniques for estimating the intensity of peoples' preferences for the environment. The weakness of orthodox utilitarian assumptions in economics concerning the commensurability of all items entering into peoples' choices is discussed. The concept of commensurability is explored as is the problem of rational choice between incommensurate alternatives. While the frequent claim that the environment has some unique moral intrinsic value is unsustainable, its preservation often raises ethical and other motivations that are not commensurate with the values that people place on ordinary marketable goods. Nevertheless, CV is also claimed to have some advantages and it is concluded that little progress will be made in this area until both sides in the debate recognise what is valid in their opponents' arguments.